Hubungan Antara Belanja Daerah Dengan Pertumbuhan Ekonomi Di Kabupaten Takalar - Rusydi, Muhammad (Jurnal Ekonomi Balance, 2011)
The purpose of this research is to know the relation of fund balance with the amount of public expenditure (development budget) in Takalar Regency and to know the amount of balancing fund at Budget of Revenue and Expenditure in Takalar Regency. The required data is obtained by collecting secondary data, ie data sourced from the Regional Development Planning Agency of Takalar Regency, the Financial and Asset Management Agency of Takalar Regency, the Central Bureau of Statistics of Takalar Regency. The data obtained then analyzed using multiple regression.The result of the research concludes that there is a positive and significant influence between the amount of balancing fund and the development expenditure. The correlation level is shown by the R value of 0.956, which means that there is a very strong relationship while the models predictive power is shown by the R Square value of 0.913 which means 91.3% of the rise and fall of development expenditure caused by the temporary balance of 8.7% due to other variables not researched.